HTTP blocking in MM: facebook.com, instagram.com (Myanmar) - Voidly (2026)
CRITICAL severity censorship detected in Myanmar. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0008
Keywords: censorship; MM; censorship; critical